2011
DOI: 10.3109/00048674.2010.534069
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging in Autism Spectrum Disorders: Preliminary Evidence of Abnormal Neural Connectivity

Abstract: Objective This study indirectly tested the hypothesis that individuals with autism spectrum disorders (ASDs) have impaired neural connections between the amygdala, fusiform face area, and superior temporal sulcus, key processing nodes of the “social brain.” This would be evidenced by abnormalities in the major fibre tracts known to connect these structures, including the inferior longitudinal fasciculus and inferior fronto-occipital fasciculus. Method Magnetic resonance diffusion tensor imaging was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 47 publications
(60 reference statements)
7
76
0
Order By: Relevance
“…39 Moreover, previously published DTI studies lend support to abnormalities of the inferior fronto-occipital fasciculus in ASD. 15,17,21,23,40,41 In the present study, the right inferior fronto-occipital fasciculus was the most severely affected association tract, which suggests a potential mechanism for known impairments in facial emotion recognition in ASD.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…39 Moreover, previously published DTI studies lend support to abnormalities of the inferior fronto-occipital fasciculus in ASD. 15,17,21,23,40,41 In the present study, the right inferior fronto-occipital fasciculus was the most severely affected association tract, which suggests a potential mechanism for known impairments in facial emotion recognition in ASD.…”
Section: Discussionmentioning
confidence: 74%
“…10 Moreover, several DTI studies also have revealed abnormalities of the left superior longitudinal fasciculus in ASD. 17,20,23,41,44 Although the important role the left superior longitudinal fasciculus has in language processing has been known since the 19th century, the importance of this structure in the right hemisphere is emerging. Abnormalities of the right superior longitudinal fasciculus also have important implications for ASD due to its connection to the superior temporal sulcus, 42 a region well known for its role in processing biologic motion, which is abnormal in ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This role for Tbr1 in callosal development is also intriguing in the context of autism. Autistic patients seem to have callosal abnormalities (19)(20)(21)(22)(23)(24)(25)(26), and in this context it is relevant that Auts2, a gene associated with autism, is regulated by Tbr1, which in turn is regulated by Satb2, a callosal fate specification gene. Recent studies suggest that a mutation in CAv1/2 (an L-type calcium channel) that is associated with Timothy syndrome, a form of autism, results in lower numbers of Satb2-expressing cells and an increase in Ctip2-expressing cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…The functional significance of this relationship has been puzzling because Tbr1 regulates corticothalamic identity, and there have been no reports of defects in corticothalamic tracts in autistic patients. However, imaging studies in patients with autism have revealed defects in callosal tracts (2,(19)(20)(21)(22)(23)(24)(25)(26). A recent publication highlights a deficit in long-range connections (such as callosal connections) and excess of short-range cortical connections in patients with autism spectrum disorder (27).…”
Section: Loss Of Tbr1 Expression In Satb2 Mutants Coincides With a Lomentioning
confidence: 99%